Assessment of Poliovirus Eradication in Japan: Genomic Analysis of Polioviruses Isolated from River Water and Sewage in Toyama Prefecture - Matsuura, Kumiko (American Society for Microbiology, 2000)
Seventy-eight poliovirus strains isolated from river water and sewage in Toyama Prefecture, Japan, during 1993 to 1995 were characterized by the PCR-restriction fragment length polymorphism (RFLP) method and by partially sequencing the VP3 and VP1 regions of the viral genome. Of these isolates, 36 were identified as Sabin vaccine strains, and 42 were identified as vaccine variant strains that had less than 1.4% nucleotide divergence from the Sabin strains, including 7 isolates with patterns different from those of Sabin strains as determined by PCR-RFLP analysis. These findings suggest that wild-type poliovirus was not circulating in Toyama Prefecture.